6x+13=-2x-19 so 8x=-19-13=-32 so x=-4
6x-y=-14 2x-3y=6
5x + x - 6x + 2x = 2x
8x-17=6x+15 8x=6x+32 (added 17 to each side) 2x=32 (subtracted 6x from each side) x=16 (divided each side by 2).
If: 2x+6x-4 = 52 Then: x = 7
6x+13=-2x-19 so 8x=-19-13=-32 so x=-4
6x - 8 + 2x - 5 = 7 - 2x ?
10
6x-y=-14 2x-3y=6
5x + x - 6x + 2x = 2x
y=6x-16 y=-2x+8
8x-17=6x+15 8x=6x+32 (added 17 to each side) 2x=32 (subtracted 6x from each side) x=16 (divided each side by 2).
If: 2x+6x-4 = 52 Then: x = 7
9+6x = 25-2x 6x+2x = 25-9 8x = 16 x = 2
2x + 9 = 6x + 1 9 - 1 = 6x - 2x 8 = 4x x = 2
2x-4=6x+8-8= -82x-12= 6x-2x= -2x-12= 4x/4=/4-3=x
6X + 3 = 2X + 19Subtract 3 from each side:6X = 2X +16Subtract 2X:4X = 16Divide by 4X = 4